2018
DOI: 10.4049/jimmunol.1602113
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of NFAT3 Due to Lack of T-Box Transcription Factor TBX5 Is Crucial for Cytokine Expression in T Cells

Abstract: The NFAT family transcription factors play crucial roles in immunological and other biological activities. NFAT3 is rarely expressed in T cells, and the mechanisms and significance of the specific NFAT3 downregulation in T cells have been unknown. In human CD4 T cells, overexpression of NFAT1 and NFAT3 enhanced and suppressed IL-2 expression, respectively. NFAT3 downregulation in Jurkat cells using RNA interference technology augmented IL-2 expression, whereas a knockdown of NFAT1, NFAT2, and NFAT4 suppressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…The expression of IL‐4 and IL‐17 was enhanced by the introduction of NFATc2 and, more vigorously, by NFATc1 . In addition to the cytokine selectivity expected with the contribution of CNBR3, we have found that endogenously expressed NFATc4 plays a suppressive role in biological functions mediated by the other NFAT isoforms . Therefore, the pharmacological and adverse effects of drugs targeting CN‐Nc3/p8‐binding are possibly more and less potent, respectively, than those of nonselective CN and NFAT inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The expression of IL‐4 and IL‐17 was enhanced by the introduction of NFATc2 and, more vigorously, by NFATc1 . In addition to the cytokine selectivity expected with the contribution of CNBR3, we have found that endogenously expressed NFATc4 plays a suppressive role in biological functions mediated by the other NFAT isoforms . Therefore, the pharmacological and adverse effects of drugs targeting CN‐Nc3/p8‐binding are possibly more and less potent, respectively, than those of nonselective CN and NFAT inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Jurkat-TAg cells were transfected with pEF-NFATc1-CNBR3 expression vector by electroporation and cultured, as described previously. 19 Total RNA was extracted from 2 × 10 5 cells with or without stimulation with 1 μM IOM plus 5 nM phorbol 12-myristate 13-acetate (PMA) for 6 hours. Using 1 μg of total RNA, cDNA was synthesized by SuperScript III reverse transcriptase (Thermo Fisher Scientific).…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
See 3 more Smart Citations